Detection of tick-borne pathogens in wild birds and their ticks in Western Siberia and high level of their mismatch - Korobitsyn, Igor G; Moskvitina, Nina S; Tyutenkov, Oleg Yu; Gashkov, Sergey I; Kononova, Yulia V; Moskvitin, Sergey S; Romanenko, Vladimir N; Mikryukova, Tamara P; Protopopova, Elena V; Kartashov, Mikhail Yu; Chausov, Eugene V; Konovalova, Svetlana N; et al. (Folia parasitologica, 2021)
The Tomsk region located in the south of Western Siberia is one of the most high-risk areas for tick-borne diseases due to elevated incidence of tick-borne encephalitis and Lyme disease in humans. Wild birds may be considered as one of the reservoirs for tick-borne pathogens and hosts for infected ticks. A high mobility of wild birds leads to unpredictable possibilities for the dissemination of tick-borne pathogens into new geographical regions. The primary goal of this study was to evaluate the prevalence of tick-borne pathogens in wild birds and ticks that feed on them as well as to determine the role of different species of birds in maintaining the tick-borne infectious foci. We analysed the samples of 443 wild birds (60 species) and 378 ticks belonging to the genus Ixodes Latraille, 1795 collected from the wild birds, for detecting occurrence of eight tick-borne pathogens, the namely tick-borne encephalitis virus (TBEV), West Nile virus (WNV), and species of Borrelia, Rickettsia, Ehrlichia, Anaplasma, Bartonella and Babesia Starcovici, 1893, using RT-PCR/or PCR and enzyme immunoassay. One or more tick-borne infection markers were detected in 43 species of birds. All markers were detected in samples collected from fieldfare Turdus pilaris Linnaeus, Blyth's reed warbler Acrocephalus dumetorum Blyth, common redstart Phoenicurus phoenicurus (Linnaeus), and common chaffinch Fringilla coelebs Linnaeus. Although all pathogens have been identified in birds and ticks, we found that in the majority of cases (75.5 %), there were mismatches of pathogens in birds and ticks collected from them. Wild birds and their ticks may play an extremely important role in the dissemination of tick-borne pathogens into different geographical regions.
Keywords: ptáci; Animals; Sibiř; Siberia; Humans; lidé; Birds; zvířata; Tick-Borne Diseases; klíště; nemoci přenášené klíšťaty; Ixodes; Borrelia